Urban and geographic aspects of building height in former provincial capitals in Poland - Czapliński, Paweł; Rubinowicz, Paweł; Gazińska, Olga; Bajor, Konrad (Quaestiones Geographicae, 2026)
Building height is a significant indicator of spatial, social, and economic changes in cities. This study aimed to analyse the variation in average building heights across former provincial capitals in Poland, which lost their administrative status following the 1999 administrative reform. The analysis covered 31 urban centres and utilised data from ALS LiDAR aerial laser scanning (digital surface model – DSM and digital terrain model – DTM) alongside BDOT10k topographic database, enabling precise assessment of building geometry. Average building heights were calculated for entire cities and within radii of 1, 2, 3 and 5 km from designated city centres. The results reveal a clear overall trend towards taller buildings being concentrated in city centres, with average building height decreasing with distance from the core. However, exceptions were identified, e.g., in Konin, where building height increases with distance from the city centre. The highest average building heights across rentier city were observed in Legnica (10.4 m), Elbląg (9.99 m), and Bielsko-Biała (9.09 m), while the lowest were recorded in Sieradz (7.70 m) and Skierniewice (7.71 m). Additionally, a k-means clustering analysis distinguished two groups of cities, revealing a tendency for taller buildings in western Poland. Statistical correlation analysis also showed a strong relationship between average building height and population size, suggesting that urbanisation and population growth are key drivers of vertical development. These findings contribute to a deeper understanding of urban development patterns in Poland and offer valuable insights for spatial planners and policymakers. The results may support sustainable urban development and more effective land-use planning, particularly in balancing growth with the quality of life for residents in the context of ongoing urbanisation.